An Improved Method for Monitoring Multiscale Plant Species Diversity of Alpine Grassland Using UAV: A Case Study in the Source Region of the Yellow River, China - Sun, Yi; Yuan, Yaxin; Luo, Yifei; Ji, Wenxiang; Bian, Qingyao; Zhu, Zequn; Wang, Jingru; Qin, Yu; He, Xiong Zhao; Li, Meng; Yi, Shuhua (Frontiers in Plant Science, 2022)
Plant species diversity (PSD) is essential in evaluating the function and developing the management and conservation strategies of grassland. However, over large region, the efficient and high precision method monitoring the multiscale PSD (α-, β- and γ-diversity) is lack. In this study, we proposed and improved an unmanned aerial vehicle (UAV)-based PSD monitoring method (UAVB) and tested the feasibility, and meanwhile, explored the potential relationships between multiscale PSD and precipitation on alpine grassland of the source region of the Yellow River (SRYR), China. Our findings showed that: 1) UAVB was more representative (larger monitoring areas and more species identified with higher α- and γ-diversity) than the traditional ground-based monitoring method, though a few specific species (small in size) were difficult to identify; 2) UAVB is suitable for monitoring multiscale PSD over large region (the SRYR in this study), and the improvement by weighing the dominance of species improved the precision of α-diversity (higher R2 and lower P values of the linear regressions); and 3) the species diversity indices (α- and β-diversity) increased first and then they tended to be stable with the increase of precipitation in SRYR. We concluded that, UAVB is suitable for monitoring multiscale PSD of alpine grassland community over large region, which will be useful for revealing the relationship of diversity-function, and helpful for conservation and sustainable management of alpine grassland.